Fauna, environment and human presence during MIS5 in the North of Spain: The new site of Valdavara 3 - Vaquero, Manuel (2019)
tValdavara 3 is a new early late Pleistocene paleontological and archeological cave site innorthwestern Iberia. Over 1400 fossils have been collected, representing about 40 species.The fauna is of interglacial aspect and is in accordance with the OSL dates from the fossilif-erous layer, which indicate an age of 103–113 ka. The great taxonomical diversity indicatesa varied landscape. A small collection of lithic artifacts was found associated with the fos-sils, demostrating presence of humans and suggesting short non-residential visits to thecave. The fossiliferous site was predominantly formed by natural processes. Many fossillocalities have short or biased faunal lists, but the fossil fauna recovered from Valdavara 3is remarkably diverse and may reflect the fauna which once lived there.